2020
DOI: 10.1177/0146167220974162
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent Effects of Positive Contact Between Women and Men on Collective Actions for Women’s Rights

Abstract: Positive intergroup contact, under some conditions, can undermine the interest of members of both socially disadvantaged and advantaged groups to act for equality. However, little is known about whether similar effects appear in a unique form of intergroup relations, gender relations. In two correlational studies and two experiments, we investigated the relationships among quality of contact, perceived discrimination, fusion with the feminist movement, and willingness to engage in collective action for women’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…Collective action research for other groups in the context of gender has primarily focused on men's intentions to engage in action for women. These studies confirm some of the SIMCA predictions by showing that men are more likely to support action advancing gender equality when they see women as the disadvantaged group (e.g., Vázquez et al., 2021), perceive gender inequality as pervasive (Iyer & Ryan, 2009), and share the sense of common cause between men and women (Subašić et al., 2018). Interestingly, some recent work in this area acknowledges that not all action for women is necessarily progressive.…”
Section: Introductionsupporting
confidence: 55%
“…Collective action research for other groups in the context of gender has primarily focused on men's intentions to engage in action for women. These studies confirm some of the SIMCA predictions by showing that men are more likely to support action advancing gender equality when they see women as the disadvantaged group (e.g., Vázquez et al., 2021), perceive gender inequality as pervasive (Iyer & Ryan, 2009), and share the sense of common cause between men and women (Subašić et al., 2018). Interestingly, some recent work in this area acknowledges that not all action for women is necessarily progressive.…”
Section: Introductionsupporting
confidence: 55%
“…This mediator is rooted in the joint household element that is a common feature of romantic relationships and has little to do with general forms of contact. Thus, the current work diverges from that of Vázquez et al (2020) in the specific focus on romantic contact and in the proposed underlining psychological mechanism.…”
Section: Romantic Relationship As Optimal Intergroup Contactmentioning
confidence: 77%
“…Recent work lends support for this idea. Vázquez et al (2020) showed that women who report having more positive contact with men, had more positive attitudes towards men (in general) and were less motivated to engage in collective action in support of women’s rights. This research, however, did not distinguish between general contact experiences that women have with men in multiple occasions (e.g., in one’s work, in one’s neighborhood, in one’s varied social circles, in one’s extended family) and contact that is part of a romantic relationship.…”
Section: Romantic Relationship As Optimal Intergroup Contactmentioning
confidence: 99%
“…Although emerging literature has been increasingly showing that intergroup contact can mobilize advantaged social groups towards collective actions supporting the disadvantaged (Hässler, Uluğ, et al, 2020), only a few studies identified the mechanisms responsible for the mobilizing effect of intergroup contact (see Di Bernardo et al, 2021; Graf & Sczesny, 2019; Kotzur et al, 2019; Reimer et al, 2017; Vazquez et al, 2021). Thus, the literature lacks a nuanced and detailed understanding of the processes triggered by intergroup contact leading the advantaged to act collectively in favor of the disadvantaged.…”
Section: Discussionmentioning
confidence: 99%